All clear! advanced - Fragiadakis, Helen Kalkstein (Heinle & Heinle Publishers, 2002)
All Clear! Advanced is the highest in a 3 book series of conversationally oriented texts. Written specifically for students at the advanced level, the text teaches students to recognize and produce over 200 high frequency idioms in ways that develop effective listening, speaking, and pronunciation skills.